2019
DOI: 10.1097/tp.0000000000002792
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes Following Kidney Transplantation From Donors With Acute Kidney Injury

Abstract: Background. Kidneys from deceased donors with acute kidney injury (AKI) are more likely to be discarded because of concerns for poor outcomes after transplantation. The aim of this study was to determine the long-term outcomes of a large cohort of patients transplanted utilizing kidneys from deceased donors with AKI. Methods. All patients receiving a deceased donor kidney transplant during a recent 10-year period were included. Acute Kidney Injury Netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 31 publications
3
67
1
Order By: Relevance
“…These outcomes are consistent with our centers' experience with solitary DCD liver and kidney allografts as well as with the most recent national UNOS data. 11,14 In this updated series on DCD SLK, we found the incidence of ischemic cholangiopathy to be low at 10.0% and no DCD liver allografts were lost to ischemic cholangiopathy within the first year (Tables 4 and 5 11,19,20 In this series, the observed DGF rates were higher in the DCD cohort (40.0% vs 23.7%) although this did not reach statistical significance ( Table 2). The length of DGF was also found to be longer in the DCD SLK cohort (median 20 vs 4 days).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…These outcomes are consistent with our centers' experience with solitary DCD liver and kidney allografts as well as with the most recent national UNOS data. 11,14 In this updated series on DCD SLK, we found the incidence of ischemic cholangiopathy to be low at 10.0% and no DCD liver allografts were lost to ischemic cholangiopathy within the first year (Tables 4 and 5 11,19,20 In this series, the observed DGF rates were higher in the DCD cohort (40.0% vs 23.7%) although this did not reach statistical significance ( Table 2). The length of DGF was also found to be longer in the DCD SLK cohort (median 20 vs 4 days).…”
Section: Discussionmentioning
confidence: 74%
“…21 More recently, we have looked at the impact of DGF in the setting of severe acute kidney injury donors, DCD donors, and extended-criterion donors (kidney donor profile index [KDPI] ≥ 85%). 11,19,20 For these donors, the observed duration of DGF is also longer (median 10 days versus 8 days) but does not impact long-term renal function recovery. 19,20 TA B L E 3 SLK biopsy results In addition, despite longer periods of DGF, we have not observed any differences on protocol biopsy specific to IFTA or fibrosis progression.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies showed that donors with AKI were associated with a higher rate of DGF 7,8,10,15 , and that the DGF rate was higher with AKIN stage 2 and 3 disease 9,16 . Similarly in our study, the DGF rate tended to increase with the donor AKI stage, especially in stage 3.…”
Section: Discussionmentioning
confidence: 93%
“…Domagala et al 10 reported nding no difference in the rate of biopsy-proven acute rejection (BPAR) episodes between donors with and without AKI in the rst year post-transplantation. Those reports thus found no relationship between donors with AKI and graft survival [7][8][9][10] . Nonetheless, debate continues regarding the use of donors with AKI.…”
Section: Introductionmentioning
confidence: 90%